Public Health Surveillance Studies of Alcohol Industry Market and Political Strategies: A Systematic Review - McCambridge, Jim (J Stud Alcohol Drugs, 2019)
OBJECTIVE: This review examines public health surveillance (PHS) studies of alcohol industry actors that explore the implications of the integration of business and political strategies for public health. METHOD: Eligible for inclusion were studies published in English language peer-reviewed journals since 1980 that sought to investigate both alcohol industry business and political strategies and their implications for public health. Studies were also required to present economic, political, and health data together. Seven databases were searched until May 2018. RESULTS: Six studies were identified as eligible for inclusion in this review, undertaken in high-, middle-, and low-income countries and published between 2000 and 2015. Political strategies are driven largely by business interests, whether at the company, sectoral, or industry level, and corporate social responsibility activities may be integrated within overall strategies. There is a high degree of collaboration in political strategy development between companies, facilitated by growing concentration among global producers operating in increasingly oligopolistic markets. There are limited insights into the dynamics of market competition and limited methodological data available. CONCLUSIONS: PHS studies play a valuable role in identifying aspects of alcohol industry strategies that warrant more detailed and carefully designed research, as well as in elucidating global health implications. Further research in PHS and other kinds of studies will assist efforts to reduce the global burden of disease caused by alcohol.